The prospective impact of new shopping centres on the retail structure of Braga. - Porfirio Guimaraes, Pedro (Bulletin of Geography. Socio-economic Series, 2014)
Following the application for two new shopping centres in the city of Braga, a medium-size city located in the North region of Portugal, the purpose of this paper is to look for evidence of the possible impacts of those commercial structures on the retail sector of Braga. An overview of the literature allows us to conclude the strong relation between retail and cities and their town centres. Recently, the process of suburbanization and the transformation in the retail sector put into question the role of those areas by transferring the consumption from town centres and traditional retail formats to new structures located on the periphery. 400 questionnaires were given to consumers to analyse the consumption habits and the way they might change with the possible arrival of two new shopping centres. We have come to the conclusion that these commercial structures are very much present in the consumption habits and in the commercial environment of consumers. They associate characteristics like quality, animation, security, cleanness, time saving, product diversity, comfort, conviviality and parking facilities with that retail format. With the implantation of new shopping centres it is expected that the existent retail sector will undergo a decrease in its importance as a shopping destination. The data from the questionnaires allow us to conclude that it is not only the already existent shopping centres that will suffer but also the other retail formats. Nevertheless, a significant number of respondents do not think of transferring the shopping they already do to the new retail structures.